2005
DOI: 10.1111/j.1365-2788.2005.00705.x
|View full text |Cite
|
Sign up to set email alerts
|

Is Post‐Traumatic Stress Disorder a helpful concept for adults with intellectual disability?

Abstract: Experienced professionals and practitioners considered most of the ideas from PTSD research with non-disabled adults to be relevant to adults with ID who experience trauma, but that some behaviour reported in research with children was also relevant. Topics and questions for use in clinical and research practice with individuals who have experienced trauma were proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
36
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 38 publications
4
36
0
Order By: Relevance
“…Behavioral problems are associated with experiencing life events (Ghaziuddin, 1988) and a potential side effect of psychiatric illness in this population group (Cooper, Melville, & Einfeld, 2003), with Marston, Perry, and Roy (1997) noting behavioral equivalents in the presentation of depression in people with intellectual disabilities. This supports modification of the general population criteria for PTSD, for example, by the inclusion of behavioral problems (McCarthy, 2001;Mitchell & Clegg, 2005), plus physical health changes (Mitchell, Clegg, & Furniss, 2006) and changes in skills (Murphy, O'Callaghan, & Clare, 2007), which have also been linked to the experience of adverse life events in people with intellectual disabilities.…”
supporting
confidence: 53%
“…Behavioral problems are associated with experiencing life events (Ghaziuddin, 1988) and a potential side effect of psychiatric illness in this population group (Cooper, Melville, & Einfeld, 2003), with Marston, Perry, and Roy (1997) noting behavioral equivalents in the presentation of depression in people with intellectual disabilities. This supports modification of the general population criteria for PTSD, for example, by the inclusion of behavioral problems (McCarthy, 2001;Mitchell & Clegg, 2005), plus physical health changes (Mitchell, Clegg, & Furniss, 2006) and changes in skills (Murphy, O'Callaghan, & Clare, 2007), which have also been linked to the experience of adverse life events in people with intellectual disabilities.…”
supporting
confidence: 53%
“…Mitchell and Clegg (2005) report that sexual abuse survivors with ID present with PTSD but that they may have additional symptoms, which may contribute to misdiagnosis. In their case-controlled study Sequiera et al (2003) found that 35% of their sample had symptoms that fulfilled the criteria for a diagnosis of PTSD.…”
mentioning
confidence: 95%
“…Very little research, however, has been conducted on traumatic experiences across the life span, except for isolated experiences, such as sexual abuse [15][16][17][18] and understanding posttraumatic stress disorder (PTSD) in PWID [19,20].…”
Section: Past Research Of Life Events and Traumatic Experiencesmentioning
confidence: 99%